Answer:
C
Step-by-step explanation:
By the definition of negative indices, we can rewrite our expression:
![y^-^\frac{4}{3} =\frac{1}{y^-^\frac{4}{3} }](https://tex.z-dn.net/?f=y%5E-%5E%5Cfrac%7B4%7D%7B3%7D%20%3D%5Cfrac%7B1%7D%7By%5E-%5E%5Cfrac%7B4%7D%7B3%7D%20%7D)
And by the definition of fraction powers, we can rewrite our term:
![\frac{1}{y^-^\frac{4}{3} }=\frac{1}{(\sqrt[3]{y})^4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7By%5E-%5E%5Cfrac%7B4%7D%7B3%7D%20%7D%3D%5Cfrac%7B1%7D%7B%28%5Csqrt%5B3%5D%7By%7D%29%5E4%7D)
Not sure if that's what C says because the picture is kinda blurry.
Answer: x = 5, y = 7
Step-by-step explanation:
1. First, put the variables together/rearrange:
y - x = 2 & 5x - 4y = -3
2. Cancel out variable x by multiply the first equation by 5:
5y - 5x = 10 & 5x - 4y = -3
3. Add equations:
y = 7
4. Then determine x by plugging y back into the first equation y = x + 2:
x = 5
Please send the information please text please thank for your information thank me please let
The value of the expression (-4x - 4) + (-4x - 10) is -8x - 14
<h3>What are expressions?</h3>
Expressions are mathematical statements that are represented by variables, coefficients and operators
<h3>How to determine the value of the expression?</h3>
The expression is given as
The sum of (-4x - 4) and (-4x - 10)
This can be represented as
(-4x - 4) + (-4x - 10)
Remove the bracket
So, we have
(-4x - 4) + (-4x - 10) = -4x - 4 - 4x - 10
Collect the like terms
So, we have
(-4x - 4) + (-4x - 10) = -4x - 4x - 4 - 10
Evaluate the like terms
So, we have
(-4x - 4) + (-4x - 10) = -8x - 14
Hence, the value of the expression (-4x - 4) + (-4x - 10) is -8x - 14
Read more about expression at
brainly.com/question/723406
#SPJ1
Answer:
210.00 divided by 4 = 52.5 then you would subtract 210 by 52.5 and you would get <u>157.5.</u>
Step-by-step explanation: